penelitian saya Rujuk Pascaiddah dalam Perspektif Fikih dan Kompilasi Hukum Islam: Studi di KUA Gudo Jombang: Indonesia - Sultan Farid; Mochammad Fahd Akbar (Justicia Religia, 2026)
This study examines the practice of post-iddah reconciliation from the perspective of Islamic jurisprudence and the Compilation of Islamic Law (KHI), based on a study conducted at the Office of Religious Affairs (KUA) in Gudo Subdistrict, Jombang Regency. The research problem stems from the discovery of reconciliation requests filed after the iddah period has ended, even though under Islamic law, the right to reconciliation applies only during the iddah period of a raj‘i divorce. Once the iddah period is over, the marital relationship changes to talak bain sughra, so that in order to reunite, a new marriage contract must be performed. This study aims to analyze the provisions regarding post-iddah reconciliation according to Islamic jurisprudence and the Compilation of Islamic Law, as well as to examine the practices of handling such cases at the KUA in Gudo, Jombang. This study employs a qualitative approach using a juridical-empirical research design. Data were collected through interviews, observations, and documentation involving the Head of the KUA, marriage officiants, and administrative staff. Data analysis was conducted through the stages of data reduction, data presentation, and the drawing of conclusions using a descriptive-analytical approach. The results of the study indicate that remarriage after the end of the iddah period does not have legal validity as a remarriage; rather, it must be carried out through a new marriage contract in accordance with the provisions of fiqh and the KHI. Practices at the Gudo KUA show that officials have directed couples to perform a new marriage contract to ensure legal certainty and the protection of civil rights.